2010
DOI: 10.1002/cphc.201000118
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Cation Translocation in a Calix[4]biscrown: Towards a New Type of Light‐Driven Molecular Shuttle

Abstract: The photophysics of a ditopic receptor of potassium ion consisting of a 1,3-alternate calix[4]biscrown with a merocyanine dye (DCM) inserted into each crown is reported. Thanks to the large difference between the binding affinity for one and two potassium ions, one can find relative total concentrations of ligand and potassium ion at which the 1:1 complex is most predominant with respect to the free ligand and the 2:1 complex whose amounts are a few percents. Investigation of the 1:1 complex by femtosecond tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 86 publications
2
16
1
Order By: Relevance
“…These evolutions are perfectly compatible with the value of the stability constants determined by steady-state measurements.This result shows that the two complexation sites are completely equivalent and there is no difference in photophysical properties between the 1:1 and 2:1 complexes. It also indicates that there is no presence of the photoejection of bound cation in the excited-state complexes as previously observed for fluoroionophores where a bound cation is in interaction with an electrondonating group conjugated with an electron-withdrawing group [40][41]. Indeed, the oxygen atoms of the crown-ether play double roles: they participate as electron-donating group in the photoinduced charge transfer process to the BODIPY moiety and they also serve as binding site to cations.…”
supporting
confidence: 56%
“…These evolutions are perfectly compatible with the value of the stability constants determined by steady-state measurements.This result shows that the two complexation sites are completely equivalent and there is no difference in photophysical properties between the 1:1 and 2:1 complexes. It also indicates that there is no presence of the photoejection of bound cation in the excited-state complexes as previously observed for fluoroionophores where a bound cation is in interaction with an electrondonating group conjugated with an electron-withdrawing group [40][41]. Indeed, the oxygen atoms of the crown-ether play double roles: they participate as electron-donating group in the photoinduced charge transfer process to the BODIPY moiety and they also serve as binding site to cations.…”
supporting
confidence: 56%
“…38,47 To characterize the dynamics of the excited state relaxation and provide further insight into the light-induced movement of the dye 2 molecule inside the CB [7] cavity, the femtosecond transient absorption spectroscopy (TRABS) was applied (see details in the ESI, † Section S6). 48 A characteristic result of a pump-probe TRABS experiment for 2, i.e. a map of absorbance changes after light excitation in delay-wavelength coordinates, is displayed in Fig.…”
mentioning
confidence: 99%
“…4 Light-induced switching in addition offers the advantage of working rapidly and precisely, both in space and time. 5 Let us note that spontaneous tunneling of K + across the calix[4]arene cavity was not detected by NMR spectroscopy of the core compound at temperatures lower than 105 1C. We showed that upon excitation of DCM at 470 nm, a positive charge was created on the nitrogen atom of the crown within the chromophore due to intramolecular charge transfer, which repels the K + ion towards the opposite crown in the picosecond timescale, without photoejection to the bulk.…”
mentioning
confidence: 84%
“…2 Molecular shuttles have been demonstrated by the, pH or redox-driven, movement of a sub-part in mechanically interlocked molecules 3 or translocation of a metal ion in a ditopic receptor. In a previous paper, 5 we reported a symmetric ditopic receptor of potassium ion, calix-DCM2, consisting of a 1,3-alternate calix [4]biscrown core with the merocyanine dye DCM (4-dicyanomethylene-2-methyl-6-pdiethylaminostyryl-4H-pyran) inserted into each crown. In a previous paper, 5 we reported a symmetric ditopic receptor of potassium ion, calix-DCM2, consisting of a 1,3-alternate calix [4]biscrown core with the merocyanine dye DCM (4-dicyanomethylene-2-methyl-6-pdiethylaminostyryl-4H-pyran) inserted into each crown.…”
mentioning
confidence: 99%